Ophthalmic pharmaceutical clinical trials: interpretation. (May 2015) - Varner, Paul
Interpretation of ophthalmic pharmaceutical clinical trials involves basic – but not in-depth – understanding of terminology and methods of statistics. Key concepts underlying statistical methodology and factors to consider regarding interpretation of clinical reports are reviewed.